Red Tunable High-Power Narrow-Spectrum External-Cavity Diode Laser Based on Tapered Amplifier - Chi, Mingjun; Jensen, Ole Bjarlin; Erbert, Götz; Sumpf, Bernd; Petersen, Paul Michael (IntechOpen, 2012)
None